Sensitive Colorimetric Detection of Interleukin-6 via Lateral Flow Assay Incorporated Silver Amplification Method - Rahbar, Mohammad; Wu, Yuling; Subramony, J. Anand; Liu, Guozhen (Frontiers in Bioengineering and Biotechnology, 2021)
Interleukin-6 (IL-6) is a pro/anti-inflammatory cytokine, the quantitative detection of which has been extensively considered for diagnosis of inflammatory associated diseases. However, there has not yet been a reliable, low-cost, and user-friendly platform developed for point-of-care (POC) detection of IL-6, which will eliminate the conventional costly, time-consuming, and complex assays. In this work, we developed a lateral flow assay (LFA) for colorimetric detection of IL-6, using anti-IL-6 antibodies conjugated to gold nanoparticles (AuNPs) as the detection probes. Silver amplification technique was incorporated with the newly developed assay in order to enhance the obtained colorimetric signals, allowing sensitive detection of IL-6 in human serum in the desired physiological ranges (i.e. 5-1000 pg/mL). A limit of detection (LOD) of 5 pg/mL could be achieved for IL-6 detection in serum with the amplification step which was not achievable in the standard assay. The corresponding specificity and reproducibility tests were all preformed to confirm the reliability of this assay for quantitative measurement of IL-6 in a POC manner.